THE CONCEPTUAL DISTINCTION BETWEEN POLISH MARKERS1 OF REFLEXTVTTY: SIEBIE AND SIĘ - Drogosz, Anna (Acta Neophilologica, 2005)
The article discusses reflexivity as a departure from the canonical event model and examines the distinction between two Polish markers of reflexivity: siebie and się. Both these markers code the direct reflexive situation type but semantically and syntactically they are not always interchangeable. This distinction is explained within Langacker’s Cognitive Grammar framework and attributed to the difference in profile, trajector/landmark alignment and construal that these markers impose on a given situation. The article suggests that siebie functions as a nominal reflexive marker, which profiles a thing, and in a reflexive construction stands as the landmark of a relation. Thus siebie imposes the construal of volitio- nality and contrastiveness, and syntactically, it is obligatory as a prepositional complement and after verbs of perception. Się is a relational reflexive, and as such it profiles a relation, and specifies the identity of trajector and landmark of a relation, which become conflated in the single participant, i.e. the referent of the sentence subject. Consequently, the się-constructions are neutral with respect to intentionality of the profiled action, and conceptually simpler than siebie-constructions, which accounts for their higher frequency of occurrence.